Pengaruh Pemberian Macam dan Dosis Pupuk Organik terhadap Beberapa Sifat Kimia Tanah, Serapan P serta Hasil Sawi (Brassica juncea L.) Pada Ultisols Asal Jatinangor - Maya Damayani (Fakultas Pertanian Universitas Padjadjaran, 2014)
The aim of this researchwas to find out the effect of kind anddoses of organic fertilizers on the pH, available P, P uptake and yield of green mustard crop (Brassica juncea L.) on Ultisols from Jatinangor. Also expected to obtain of kind and doses organic fertilizer that produces the best green mustard plants on Ultisols from Jatinangor. Experiments conducted from September to December 2011 in the greenhouse garden experiment Faculty of Agriculture, Padjadjaran University, Jatinangor, Sumedang Regency, West Java with 780 meters altitude above sea level. Organic fertilizers are used in this experiment was casting, straw compost and sheepmanure. The dose used was 20 tons ha1 and 30 tons ha-1 for each of the organicfertilizers, and onetreatment using a combination of all three doses of 10 tha-1 for each kind of organic fertilizer in combination.The Experimental design was used Randomized Design Group (RAK) factorial pattern, consisting of one factor with eight treatments and three replicationsThe experimental results show the kinds and doses of organic fertilizers do not give a real difference for P uptake and Yield of crop mustard greens on Ultisols Jatinangor.But there is a real difference to the pH and available P, especially with treatment using a combination of casting 10 t ha-1, straw compost 10 t ha-1, and sheep manure 10 t ha-1.